Antibacterial and antifungal effectiveness of Turbinaria conoides as a denture cleanser: Efektivitas antibakteri dan antifungi Turbinaria conoides sebagai denture cleanser - Asmawati; Maulfi Amanda Muktar; Nurul Adinda Takwin; Muhammad Zulfikar Akbar Pattisahusiwa (Makassar Dental Journal, 2022)
One of the riches of the earth that can be found in the sea is brown macroalgae (seaweed). Brown macroalgae has various pro-perties such as having antibacterial and antifungal properties. One type of macroalgae that is commonly found in Indonesia is Turbinaria conoides. T.conoides has been studied for its many benefits, including relieving fever in children, insect repellent, fertilizer, and also as an antifungal and antibacterial agent. The components found in the extract of T.conoides were investiga-ted to be able to inhibit C.albicans and also have antibacterial properties. Because it has antibacterial and antifungal properties,T. conoides has the potential to be used as the main ingredient for making denture cleansers that are safe, inexpensive, and bio-compatible.